Beyond Digital Transformation: Digital Technology as Mediator For Strategic MSME Performance in Demak - Sulistyorini; Ayu Nurafni Octavia; Any Setyarini (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The rising prominence of the digital economy has heightened the need for MSMEs in Demak Regency to adopt digital technologies. However, many MSMEs face challenges in effectively utilizing these technologies to enhance their performance. This study addresses the research gap by examining the mixed results in prior studies on the impact of business strategy and technopreneurship on MSMEs' performance.Purpose: The study will investigate the key determinants of MSMEs' performance in Demak Regency and the intermediary role of digital technology. It examines how business strategy and technopreneurship, through digital technology, influence MSMEs' performance.Design/Methodology/Approach: This research adopts a quantitative method by collecting data from 109 MSME respondents in Demak Regency through convenience and non-probability sampling. The study analyzes the connections among business strategy, technopreneurship, digital technology, and MSMEs' performance using SmartPLS version 4.Finding/Result: The data suggests that business strategy and technopreneurship are positively tied to the adoption of digital technology. Business strategy significantly boosts MSMEs' performance, whereas technopreneurship, despite a positive trend, isn't statistically significant. Digital technology substantially improves performance, mediating business strategies' and technopreneurship's influence on MSME success.Conclusion: Strategic planning and innovation in technology play essential roles in promoting the adoption of digital tools and improving MSME performance. Digital technology acts as a key mediator that strengthens these relationships. As a result, MSMEs are encouraged to improve digital literacy and infrastructure, and policy support remains crucial in fostering an environment that supports digital adoption.Original/value (state of the art): This study offers new insights into the elements that influence MSMEs' performance in the digital economy, highlighting the importance of strategic management and technological adoption. The findings hold value for both policymakers and business practitioners. Keywords: business strategy, technopreneurship, digital technology, MSMEs performance